Penyelesaian Sengketa Merek PS Glow Melawan MS Glow Berdasarkan Undang-Undang No. 30 Tahun 1999 Tentang Arbitrase Dan Alternatif Penyelesaian Sengketa - Novi Yanti; Devi Siti Hamzah Marpaung (Jurnal Ilmiah Wahana Pendidikan, 2022)
Trademarks are images, logos, names, words, letters, numbers, color schemes, two and/or three dimensions, sounds, holograms, or a combination of the two dimensions. The above factors are to distinguish goods and/or services produced by individuals or legal entities in the context of trading goods and/or services. The existence of a brand system aims to prevent trademark disputes between brand owners. Regarding dispute resolution methods, business/commercial disputes can be resolved in court or out of court. The author's research is a form of normative legal research that is descriptive in nature, and analyzes the legal problems faced by this research data collection method by considering the laws and regulations and constitutional provisions in legal theory. Conducted by a library survey, the data analysis technique used in this survey is a qualitative method. The analytical methodology includes general data regarding legal opinions contained in the law, namely Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. According to Articles 76 to 84 of Law Number 20 of 2016 concerning Marks and Geographical Indications, trademark disputes can be resolved in two ways: litigation and non-litigation.